Aktualisasi Hukum Islam dalam Upaya Pelestarian Lingkungan Hidup - Widuri, Endang (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
Human beings have to preserve the nature and to avoid the environment damaging. To do that, there should be internalization on obeying laws. UU no 23 th. 1997 will only be a concept till Indonesia citizens are able to apply it daily as good Moslems and good citizens.